Dermatology case - Adrião, Mariana; Sarmento, João; Barreira, João (BIRTH AND GROWTH MEDICAL JOURNAL, 2018)
Acute hemorrhagic edema of infancy (AHEI) is a small vessels leukocytoclastic vasculitis which typically occurs between 4 and 24 months. It manifests with palpable purpuric skin lesions and extremities’ edema. We describe the clinical case of an 18 month-old child brought to the Emergency Room due to purpuric skin lesions distributed throughout his limbs and face with about 12 hours of evolution. Due to the well-being and the normal analytic study, the diagnosis of AHEI was presumed. The progress of the skin lesions was evaluated, with follow-up at 48 hours and seven days after the beginning of the lesions. It was possible to note their evolution and disappearing after three weeks. AHEI is a self-limited disease, with a benign course, which contrasts with its exuberant purpuric skin lesions. Among its principals differential diagnosis is Henoch-Schonlein Purpura. It is important to recognize this disease, avoiding unnecessary treatments and concerns.